Patterns in classroom information propagation and word adjacency networks - Roxas, Ranzivelle Marianne Laygo (Quezon City College of Science, University of the Philippines, 2010)
Patterns are ubiquitous. These patterns contain information on the structure and underlying mechanism of a system. This study aims to investigate patterns that arise in complex systems such as social and language networks. In particular, we want to characterize the propagation of information in a classroom and probe the effect of external; factors such as seating arrangement, class size, homogeneity and motivation to the learning process. In language networks, we propose to disambiguate poem from prose and detect genre boundaries in written text by analyzing the topology and statistics of word adjacency networks.We developed a set of lectures modified from the Peer Instruction Method proposed by Dr. Eric Mazur. The materials were used in experimental lectures conducted on secondary and tertiary level students. The obtained data were used to train a two layer neural network in probing the essential attributes that drive the spatial propagation of information such as seating arrangement, class size and class homogeneity. In another experiment, the students are divided into groups and are made to compete with other groups. The resulting gain in their performance was analyzed In word adjacency networks, we utilized the network structure of literary genres for disambiguation and genre boundary detection. Network metrics such as the average path length, diameter, degree distribution, and clustering coefficient were calculated. The optimum parameters that disambiguate the two genres were determined using effect size criterion. Using these parameters, classification was done through linear discriminant analysis. A moving window was introduced to the text to detect genre boundaries. Investigating how patterns and structure found in written texts are related to its content has become important since there is a greater need for tools to categorize and manage the available resources and voluminous information online.
Vita.
Thesis (Ph.D.Physics)--University of the Philippines Diliman
Keywords: Information networks; Classroom management